Complex Regulation of gamma-Secretase: from Obligatory to Modulatory Subunits - Gertsik, Natalya; Chiu, Danica; LI, Yueming (Frontiers in Aging Neuroscience, 2015)
γ-Secretase is a four subunit, 19-pass transmembrane enzyme that cleaves amyloid precursor protein (APP), catalyzing the formation of amyloid beta (Aβ) peptides that form amyloid plaques, which contribute to Alzheimer’s disease (AD) pathogenesis. γ-Secretase also cleaves Notch, among many other type I transmembrane substrates. Despite its seemingly promiscuous enzymatic capacity, γ-secretase activity is tightly regulated. This regulation is a function of many cellular entities, including but not limited to the essential γ-secretase subunits, nonessential (modulatory) subunits, and γ-secretase substrates. Regulation is also accomplished by an array of cellular events, such as presenilin (active subunit of γ-secretase) endoproteolysis and hypoxia. In this review we discuss how γ-secretase is regulated with the hope that an advanced understanding of these mechanisms will aid in the development of effective therapeutics for γ-secretase-associated diseases like AD and Notch-addicted cancer.